Evaluation of macrophage plasticity in brown and white adipose tissue - Ortega, M. Teresa; Xie, Linglin; Mora, Silvia; Chapes, Stephen K. (My University, 2012)
There are still questions about whether macrophage differentiation is predetermined or is induced in response to tissue microenvironments. C2D macrophage cells reside early in the macrophage lineage in vitro, but differentiate to a more mature phenotype after adoptive transfer to the peritoneal cavity (PEC-C2D). Since C2D macrophage cells also traffic to adipose tissue after adoptive transfer, we explored the impact of white adipose tissue (WAT), brown adipose tissue (BAT) and in vitro cultured adipocytes on C2D macrophage cells. When PEC-C2D macrophage cells were cultured with preadipocytes the cells stretched out and CD11b and Mac-2 expression was lower compared to PEC-C2D macrophage cells placed in vitro alone. In contrast, PEC-C2D cells co-cultured with adipocytes maintained smaller, round morphology and more cells expressed Mac-2 compared to PEC-C2D co-cultured with preadipocytes. After intraperitoneal injection, C2D macrophage cells migrated into both WAT and BAT. A higher percentage of C2D macrophage cells isolated from WAT (WAT-C2D) expressed Ly-6C (33%), CD11b (11%), Mac-2 (11%) and F4/80 (29%) compared to C2D macrophage cells isolated from BAT (BAT-C2D). Overall, BAT-C2D macrophage cells had reduced expression of many cytokine, chemokine and receptor gene transcripts when compared to in vitro grown C2D macrophages, while WAT-C2D macrophage cells and PEC-C2D up-regulated many of these gene transcripts. These data suggest that the C2D macrophage phenotype can change rapidly and distinct phenotypes are induced by different microenvironments.
Keywords: Macrophage; Plasticity; Adipocyte; Adipose tissue; Trafficking